An acoustic study of the monophthongs of Ulu Terengganu Malay Dialect / Siti Nadiah Nuwawi - Siti Nadiah , Nuwawi (2020)
Amongst sub-dialects spoken in the region of Terengganu, the dialect of Ulu Terengganu Malay is the most incomprehensible variety that varies greatly in the aspects of pronunciation and lexical as compared to the standard Terengganu dialect. However, the uniqueness of the language is insufficiently addressed by academic scholars, especially acoustic features of the dialect. Through an acoustic analysis method, this research attempted to investigate the quality of monophthongs produced by the Ulu Terengganu Malay speakers. The data was collected from a group of male and female Ulu Terengganu Malay speakers. A word list and pictures were used as instruments in the data collection procedures. The F1 and F2 values of the monophthongs shown through the waveforms and spectrogram in PRAAT were measured and analysed. The independent sample t-test was used in order to further identify the vowels produced by the male and female speakers. The results showed that the monophthongs; /i/, /a/, /ə/ and /e/ that were produced by the Ulu Terengganu Malay speakers found to be similar with those reported in previous similar studies, whereas five other identified monophthongs; /ɛ/, /æ/, /ɔ/, /ɒ/ and /u/ demonstrated distinctive phonetic traits. The findings have also proven that there are eight vowels present in the Ulu Terengganu Malay dialect which are /i/, /e/, /ɛ/, /a/, /ə/, /ɔ/, /ɒ/ and /u/ and the vowels were significantly different between genders.